Delirium After Transcatheter Aortic Valve Implantation Under General Anesthesia: Incidence, Predictors, and Relation to Long‐Term Survival. Issue 11 (25th July 2019) - van der Wulp, Kees; van Wely, Marleen; van Heijningen, Lars; van Bakel, Bram; Schoon, Yvonne; Verkroost, Michel; Gehlmann, Helmut; Van Garsse, Leen; Vart, Priya; Kievit, Peter; Rikkert, Marcel Olde; Morshuis, Wim; et al.
Abstract : BACKGROUND/OBJECTIVES: Prospectively collected data on postoperative delirium (POD) after transcatheter aortic valve implantation (TAVI) are scarce. The aim of this study was to report the incidence and risk factors of delirium after TAVI under general anesthesia and to assess the association of POD with clinical outcome and short‐ and long‐term survival. DESIGN: Prospective cohort study. SETTING: Academic medical center. PARTICIPANTS: A total of 703 subsequent patients undergoing TAVI under general anesthesia between 2008 and 2017. MEASUREMENTS: Delirium was assessed according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition ( DSM‐IV ), criteria. Outcomes were postprocedural clinical outcome and short‐ and long‐term survival (30 days and 5 years, respectively). RESULTS: POD was observed in 16.5% (116/703), was the strongest independent predictor of long‐term mortality (hazard ratio = 1.91; 95% confidence interval [CI] = 1.36‐2.70), and was associated with impaired 30‐day and 5‐year survival (92.2% vs 96.8% [ P = .025] and 40.0% vs 50.0% [ P = .007], respectively). Stroke and new onset of atrial fibrillation were more often observed in delirious patients (6.9% vs 1.9% and 12.1% vs 5.1%, respectively). Strongest independent predictors of POD were prior delirium (odds ratio [OR] = 2.56; 95% CI = 1.52‐4.31) and aortic valve area less than 0.75 cm 2 (OR = 2.39; 95% CI = 1.53‐3.74). CONCLUSION: One in six patients experienced POD after TAVI under general anesthesia. POD was the strongest predictor of long‐term mortality and was associated with impaired short‐ and long‐term survival. Prior delirium and a more calcified aortic valve were the strongest independent predictors of POD. J Am Geriatr Soc 67:2325–2330, 2019